Character Installation in Early Children in The Family - Luluk Isroful Khoiriyah; Siti Choiriyah; Hamdan Magribi (AMIN: International Journal of Islamic Education and Knowledge Integration, 2023)
The Importance of Character Education in Early Childhood and the Role of Parents in its Implementation. Children are considered a test for parents and are a trust that must be safeguarded carefully. Parents who are preoccupied with their careers and pay insufficient attention to their children's education may face difficulties in addressing this test. Character education is viewed as the foundation for a child's future development. Unfortunately, many parents neglect character education, resulting in issues such as promiscuity and moral crises. Therefore, parental awareness is necessary to enhance their knowledge and experience in effectively educating their children. Character education should commence early through the wise and unbiased provision of love and affection with the goal of shaping a positive personality. Furthermore, instilling a sense of love in truth is essential. This process requires patience, perseverance, and consistency from parents and caregivers. By setting a good example, maintaining open communication, and employing appropriate methods, children can internalize positive character traits that will aid them in becoming responsible and virtuous individuals in the future. The seriousness of parents in selecting references and methods for character education is also crucial in this process